2021
DOI: 10.1111/epi.16846
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of minimally invasive and traditional surgical approaches for refractory mesial temporal lobe epilepsy: A systematic review and meta‐analysis of outcomes

Abstract: Magnetic resonance‐guided laser interstitial laser therapy (MRgLITT) and radiofrequency ablation (RFA) represent two minimally invasive methods for the treatment of drug‐refractory mesial temporal lobe epilepsy (mTLE). We performed a systematic review and a meta‐analysis to compare outcomes and complications between MRgLITT, RFA, and conventional surgical approaches to the temporal lobe (i.e., anterior temporal lobe resection [ATL] or selective amygdalohippocampectomy [sAHE]). Forty‐three studies (13 MRgLITT, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 76 publications
(237 reference statements)
3
47
2
1
Order By: Relevance
“…This means that with the small sample sizes present in most publications, studies may have been underpowered to detect statistically significant differences in seizure freedom between interventions. A meta-analysis comparing seizure free outcomes between ATLR, SAH, RF-TC and LITT was recently published which concluded that LITT was significantly less effective than open surgery ( 67 ). There are, however, significant methodological differences between our study.…”
Section: Limitationsmentioning
confidence: 99%
“…This means that with the small sample sizes present in most publications, studies may have been underpowered to detect statistically significant differences in seizure freedom between interventions. A meta-analysis comparing seizure free outcomes between ATLR, SAH, RF-TC and LITT was recently published which concluded that LITT was significantly less effective than open surgery ( 67 ). There are, however, significant methodological differences between our study.…”
Section: Limitationsmentioning
confidence: 99%
“… 31 Furthermore, the cumulative evidence indicated that the selective treatment to the HIP or to the mesial temporal structures were inferior to the anterior temporal lobectomy in terms of the chance of seizure freedom. 32 , 33 The finding of the elevated uptake of [ 11 C]K-2 in the lateral temporal cortex might be useful for the prediction of treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…We test this hypothesis using the problem of predicting surgical outcomes after stereotactic laser amygdalohippocampectomy (SLAH). A recent meta‐analysis of 10 studies found that the presence of mesial temporal sclerosis (MTS) predicted a better chance (63% vs 42%) of seizure freedom after SLAH when MTS was present than when absent 4 . However, most individual studies did not detect this effect, as their low sample size limited statistical power.…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis of 10 studies found that the presence of mesial temporal sclerosis (MTS) predicted a better chance (63% vs 42%) of seizure freedom after SLAH when MTS was present than when absent. 4 However, most individual studies did not detect this effect, as their low sample size limited statistical power. We specifically hypothesize that using ordinal logistic regression we will meaningfully increase the statistical power to detect the known relation between MTS and seizure outcome in each study.…”
Section: Introductionmentioning
confidence: 99%